2006
DOI: 10.1128/iai.01787-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protection Afforded by Brucella abortus and Brucella melitensis Unmarked Deletion Mutants Exhibiting Different Rates of Clearance in BALB/c Mice

Abstract: Research for novel Brucella vaccines has focused upon the development of live vaccine strains, which have proven more efficacious than killed or subunit vaccines. In an effort to develop improved vaccines, signaturetagged mutant banks were screened to identify mutants attenuated for survival. Mutants selected from these screens exhibited various degrees of attenuation characterized by the rate of clearance, ranging from a failure to grow in macrophages after 24 h of infection to a failure to persist in the mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 49 publications
5
71
1
1
Order By: Relevance
“…While, the percentages of abortion in pregnant cows suffering from brucellosis collected from individual animals were 2.29 %, 1.41 %, 2.59 % and 2.83 % for yeas 2008, 2009, 2010 and 2011 respectively. These results were lower than those reported by [28,29,30] whose recorded 16.1 %, 37.4 %, and 26 %, respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…While, the percentages of abortion in pregnant cows suffering from brucellosis collected from individual animals were 2.29 %, 1.41 %, 2.59 % and 2.83 % for yeas 2008, 2009, 2010 and 2011 respectively. These results were lower than those reported by [28,29,30] whose recorded 16.1 %, 37.4 %, and 26 %, respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…To construct the plasmids for deleting cydC, cydD Table 2. Using previously published methods (Kahl-McDonagh & Ficht, 2006;, the respective plasmids pEX18DcydC, pEX18DcydD and pEX18DpurD were created by a two-round PCR amplification, restricted digestion and ligation, and then introduced into RB51 and the RB51DcydC mutant via electroporation. Transformants were selected in the presence of 100 mg carbenicillin ml 21 for the first screening and 5 % sucrose for the second screening.…”
Section: Methodsmentioning
confidence: 99%
“…However, we had reason to believe that the ⌬asd mutant would be more effective than previous live attenuated strains. It has been shown that a more protective immune response can be achieved by increasing short-term vaccine persistence, which we attempted with the booster vaccine (5,23,45). Unfortunately, while vaccination with the ⌬asd mutant did indeed protect against acute melioidosis, the vaccine failed to protect against chronic melioidosis.…”
Section: Fig 6 (A)mentioning
confidence: 99%